Modern Economic Conditions and Impact of the Tax Regime on the Legalization of Self-Employment: Russian and Foreign Experience - Bolonina, E.V.; Khafizova, A.R.; Nasyrova, V. I (International Journal of Criminology and Sociology, 2022)
This article analyzes Russian and international experience in approaches to taxation of self-employed individuals and their impact on the legalization of activities based on modern economic conditions. The purpose of the study is to conduct a comparative characteristic of the criteria for determining self-employed persons and various forms of their taxation in Russia and abroad at the present stage. The special tax regime for the self-employed in Russia has been in effect since 2019 and is one of the youngest in the tax system, so the analysis of foreign experience in the taxation of self-employed persons is of particular practical interest. The authors analyze global statistics on the number of self-employed persons and identify trends in their changes not only in the Russian Federation, but also in some foreign countries, especially in the light of the development of digital technologies and the emergence of new opportunities for independent activity by individuals. The research made it possible to draw intermediate conclusions for Russia at this stage of the new regime implementation: whether modern tax regimes stimulate the development of self-employment, how optimal these regimes are for legalizing citizens ’ income, and what trends of foreign countries in the field of self-employed taxation may be relevant for modern Russia.